Development of an Elderly Health Promotion Model Through Community Participation in Mueang District, Buri Ram Province - Saengngam, Thawaree; Bonkhunthod, Punnathut; Chaiwong, Narongkorn; Maneepun, Nichaphat; Nugoonsawat, Penpis (Journal of The Royal Thai Army Nurses, 2025)
This study is a participatory action research aimed at developing a model for promoting the well-being of the elderly through community participation in a specific district of Mueang, Buri Ram Province. The sample was divided into two groups: 132 elderly individuals selected based on Krejcie and Morgan’s table and 30 representatives from healthcare service networks selected through purposive sampling. The research instruments used for data collection and their reliability coefficients included the WHO Quality of Life Questionnaire for the Elderly (WHOQOL-BREF-THAI) with a reliability of 0.93, a holistic elderly well-being assessment tool with a reliability of 0.95, and a satisfaction assessment tool with a reliability of 0.86. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through content analysis. The research findings indicated that after participating in the well-being promotion program, the elderly group showed an increase in perceived well-being and quality of life scores. Additionally, the satisfaction level of the community network partners regarding the development process of the elderly well-being promotion innovation through community participation was high, with an average score of 4.35 (S.D. = 0.60). The evaluation of the development process and the success factors in implementing the elderly well-being promotion model through community participation also showed a high level of satisfaction among community network partners, with an average score of 4.35 (S.D. = 0.60).